Resource use in small rubber holdings in Assam - Maibangsa M; Subramanian S R (Journal of Plantation Crops, 2001)
The resource use and labour requirement and tapping stage of small scale rubber plantations in Assam have been examined in this study. It was found that labour was the most important item of resource used for establishment constituting more than 50 per cent of the total expenditure. Manures and fertilizers were the next important resources used in rubber plantation accounting for 36.65 and 12.72 per cent of the total expenditure during the establishment and tapping period respectively. Labour requirement for one hectare of rubber plantation was also examined in the present study. It is revealed that 637.29 mandays are required for establishing one hectare of rubber plantation and 240.67 mandays are required for maintenance from the tapping stage onwards. Maximum percentage of labour was contributed by male labour. From the above findings it is indicated that expansion of small scale rubber plantations in Assam will contribute towards increased employment in the state, through promotion and setting up of agro-industries related with the rubber plantation sector.
Keywords: Assam; Labour requirement; Resource use; Rubber holdings